Hemotropic pathogens in aborted fetuses of domestic ruminants: transplacental transmission and implications for reproductive loss - Žilić, Daria Jurković; Naletilić, Šimun; Mihaljević, Željko; Gagović, Ema; Špičić, Silvio; Reil, Irena; Duvnjak, Sanja; Tuk, Maja Zdelar; Hodžić, Adnan; Beck, Relja (Frontiers in Microbiology, 2025)
ObjectiveHemotropic pathogens of the genera Anaplasma, Babesia, Theileria, and hemotropic Mycoplasma are significant infectious agents in domestic ruminants, most commonly associated with vector-borne transmission. However, their potential for transplacental transmission and their contribution to reproductive disorders remains poorly understood. This study aimed to investigate the presence of hemopathogens in aborted fetuses of cattle, sheep, and goats in Croatia, and to evaluate their potential role in transplacental transmission.MethodsMolecular analyses were conducted on tissue samples from 651 aborted fetuses collected between 2016 and 2019 as part of national abortion surveillance programs. PCR screening followed by sequencing were used to detect Anaplasmataceae, Babesia, Theileria, and hemotropic Mycoplasma.ResultsThirteen hemopathogens were detected in 94 of 651 fetuses (14.44%), including Anaplasma marginale, Anaplasma ovis, Anaplasma phagocytophilum, Theileria orientalis, Theileria ovis, Theileria sp. OT3, Babesia ovis, Babesia canis, Babesia vulpes, Mycoplasma wenyonii, Mycoplasma haemobos, Mycoplasma ovis, and Mycoplasma haemominutum. The highest infection rates were observed in cattle (17.27%) and sheep (15.85%), while goats showed significantly lower prevalence (5.3%). A. marginale and A. ovis were the most frequently detected pathogens in bovine and ovine fetuses, respectively. Hemotropic mycoplasmas were reported for the first time in Croatia, with the first Western Balkan record of ‘Candidatus M. haemobos’. Our study represents the first molecular documentation of a wide array of hemopathogens in aborted ruminant fetuses in Croatia, strongly indicating the possibility of transplacental transmission. The detection of species-specific patterns and the unexpected identification of protozoan species typically associated with canines highlight complex epidemiological dynamics.ConclusionVertical transmission of the detected pathogens may play a role in abortion in endemic regions and should be integrated into differential diagnostic protocols for reproductive failure investigations.